1998
DOI: 10.1042/bj3340547
|View full text |Cite
|
Sign up to set email alerts
|

Specific alterations in levels of mannose 6-phosphorylated glycoproteins in different neuronal ceroid lipofuscinoses

Abstract: Mannose 6-phosphate (Man-6-P) is a carbohydrate modification that is generated on newly synthesized lysosomal proteins. This modification is specifically recognized by two Man-6-P receptors that direct the vesicular transport of the lysosomal enzymes from the Golgi to a prelysosomal compartment. The Man-6-P is rapidly removed in the lysosome of most cell types; however, in neurons the Man-6-P modification persists. In this study we have examined the spectrum of Man-6-P-containing glycoproteins in brain specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 14 publications
5
41
0
Order By: Relevance
“…The NCL share clinical manifestations, biochemistry, and pathology, hence their classification together (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). It is probable that all of the NCL genes belong to a common metabolic pathway (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCL share clinical manifestations, biochemistry, and pathology, hence their classification together (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). It is probable that all of the NCL genes belong to a common metabolic pathway (15).…”
Section: Discussionmentioning
confidence: 99%
“…They are implicated in the pathogenesis of neurodegenerative diseases such as Alzheimer's and prion diseases (14). NCL protein deficiencies result in similar cell biologic phenotypes including dysregulated cell growth, apoptosis, and abnormal sphingolipid/phospholipid levels in CLN1-, CLN2-, CLN3-, CLN6-, and CLN8-deficient cells and neurodegeneration (1).…”
mentioning
confidence: 99%
“…Measurement of TPP1 activity was used as an indicator of compensatory upregulation of lysosomal enzyme activity, typical of many lysosomal storage disorders. TPP1 is deficient in the infantile form of NCL (Sleat et al, 1997), and TPP-1 activity was found previously to be enhanced in Cln3 ⌬ex1-6 mice (Mitchison et al, 1999) and in JNCL patients (Sleat et al, 1998). Cerebellar lysates from 1-and 6-month-old mice were analyzed for TPP1 activity (Fig.…”
Section: Cln3mentioning
confidence: 99%
“…Glycosidase activities were measured using 4-methylumbelliferyl (4-MU) substrates described by Sleat et al [6] Protease assays using amino-4-methylcoumarin (AMC) substrates have been described by Sleat et al [7] and Sohar et al [8] Reactions were initiated by adding 40 L substrate (various concentration 20 mol/L), buffer (100 mmol/ L) solution to 5 L (CB) or 10 L (other enzymes) of sample (after centrifugation, supernatants were diluted 2-, 4-and 8-fold in homogenization buffer in duplicate), incubated at 37 ℃, and terminated by the addition of 100 L of 0.5 mol/L glycine, pH10.5 (at 4-MU substrates) or 0. 1 mol/L monochloroacetic acid in 0.1 mol/L acetate, pH4.3 (AMC substrates).…”
Section: Methodsmentioning
confidence: 99%